2017
DOI: 10.1002/anie.201707996
|View full text |Cite
|
Sign up to set email alerts
|

Heterologous Expression, Biosynthetic Studies, and Ecological Function of the Selective Gq‐Signaling Inhibitor FR900359

Abstract: The cyclic depsipeptide FR900359 (FR), isolated from the tropical plant Ardisia crenata, is a strong and selective inhibitor of Gq proteins, making it an indispensable pharmacological tool to study Gq-related processes, as well as a promising drug candidate. Gq inhibition is a novel mode of action for defense chemicals and crucial for the ecological function of FR, as shown by in vivo experiments in mice, its affinity to insect Gq proteins, and insect toxicity studies. The uncultured endosymbiont of A. crenata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
99
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(101 citation statements)
references
References 31 publications
1
99
0
1
Order By: Relevance
“…MD simulation studies of Gα q protein in complex with FR and YM, respectively, indicated that the kinetic differences are largely contributed by the isopropyl (R 2 in Figure b) interaction with Phe75 in the binding pocket. The new tracers will allow to study binding kinetics of other compounds that bind to the same site, for example, novel analogues and derivatives of YM and FR, that are accessible by chemical synthesis (Rensing, Uppal, Blumer, & Moeller, ; Xiong et al, ; Zhang et al, ), and by biotechnological approaches (Crüsemann et al, ; Taniguchi et al, ). The new tracers will help to design and develop G q inhibitors with specific, desired kinetic profiles.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…MD simulation studies of Gα q protein in complex with FR and YM, respectively, indicated that the kinetic differences are largely contributed by the isopropyl (R 2 in Figure b) interaction with Phe75 in the binding pocket. The new tracers will allow to study binding kinetics of other compounds that bind to the same site, for example, novel analogues and derivatives of YM and FR, that are accessible by chemical synthesis (Rensing, Uppal, Blumer, & Moeller, ; Xiong et al, ; Zhang et al, ), and by biotechnological approaches (Crüsemann et al, ; Taniguchi et al, ). The new tracers will help to design and develop G q inhibitors with specific, desired kinetic profiles.…”
Section: Resultsmentioning
confidence: 99%
“…YM is produced by Chromobacterium sp. (Taniguchi et al, ), while FR was isolated from the plant Ardisia crenata Sims and is produced by the bacterial endophyte Candidatus Burkholderia crenata that is present as a symbiont in the leaves of the plant (Crüsemann et al, ; Fujioka, Koda, & Morimoto, ). A few analogues of FR have also been isolated, however, in tiny amounts (Crüsemann et al, ; Reher et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Synthetic FR900359 has been pharmacologically characterized on G q ‐, G s ‐, and G i ‐mediated signaling and compared to natural (isolated) FR900359, showing identical biological activity (Figure ). Recently, Crüsemann et al reported the first heterologous biosynthesis of FR900359 in a cultivable, bacterial ( Escherichia coli ) host by expression of the FR nonribosomal peptide synthetase (frs) genes, which were revealed by sequencing the uncultured endosymbiont of A. crenata …”
Section: Selective Gq Inhibitorsmentioning
confidence: 99%
“…Burkholderia leaf nodule symbionts show extensive signs of reductive genome evolution, with coding capacities ranging from 41.7 % to 67.3 % and an accumulation of pseudogenes and insertion sequences [1012]. Despite extensive genome erosion, some symbionts have been shown to produce secondary metabolites, likely involved in the protection of the host from herbivory, such as the insecticidal kirkamide and the depsipeptide FR900359, as well as the herbicidal streptol-glucoside possibly involved in allelopathic interactions [1214]. Because of genomic instability and evolved co-dependence, it is unclear whether secondary metabolism was present in the ancestor of leaf nodule Burkholderia or acquired as a secondary trait.…”
Section: Introductionmentioning
confidence: 99%